IMPLEMENTASI KETERAMPILAN PEMBELAJARAN ABAD 21 BERORIENTASI KURIKULUM MERDEKA MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DI SEKOLAH DASAR - Nurin Ainani Arifah; Ratnasari Diah Utami (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2023)
Education in Indonesia has developed. The government launched an independent curriculum by implementing a project to strengthen the profile of Pancasila students who can answer the challenges of the times by applying 21st century learning skills which include 4C (communication, collaboration, creativity, and critical thinking). This study aims to describe how the planning, implementation process, and evaluation of projects to strengthen the profile of Pancasila students in implementing 21st century learning skills oriented to an independent curriculum in elementary schools. The research method used was qualitative by describing the conditions in the field in detail and depth. Data collection techniques in the research conducted included interviews, observation, and documentation. Testing the validity of the data was carried out using the triangulation method, namely comparing and re-checking findings from various sources and different techniques. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of this study are: 1) Project planning, which includes forming a team/group as a facilitator or project implementer, knowing what the school readiness stage is in implementing the project, establishing dimensions, themes, and project time allocation, preparing project modules, and designing an assessment of the results reporting project, 2) The process of implementing the project, namely through the introduction, contextual, action, and share stages, 3) Evaluation of the project, namely by conducting formative, summative, and diagnostic assessments through the implementation of work titles. The implementation of 21st century learning skills can be applied to projects to strengthen the profile of Pancasila students by implementing 4C